Strategi Pembelajaran Al-Qur’an di Pondok Pesantren Mambaul Falah Tambilung Bawean Gresik - Khofifuddin Khofifuddin; Faridatul Hasanah; Mohammad Rafli (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Al-Qur'an learning strategies are basically learning tools to educate children who are experts in the Qur'an, especially among Islamic boarding schools and the general public. The Mambaul Falah Islamic Boarding School also makes efforts to ward off wrong perceptions of learning from Islamic law, by trying to maintain the reading of the Koran and introducing students to be more focused on reading the Koran in accordance with the correct qaidah. From the description above, researchers can focus on research problems as follows; 1). What is the strategy for organizing Al-Qur'an learning at the Mambaul Falah Islamic Boarding School? 2). What is the strategy for delivering Al-Qur'an learning at the Mambaul Falah Islamic Boarding School? 3). What is the strategy for managing Al-Qur'an learning at the Mambaul Falah Islamic Boarding School? This research is a field research (field research) using a qualitative research model with a qualitative descriptive method. The important idea of field research is that researchers come directly to the field by observing a phenomenon about a natural state. This research seeks to describe phenomena from the aspect of natural conditions, holistically, and seeks to find meaning. In this case the researcher will observe, describe, and explain the learning strategies at the Mambaul Falah Islamic Boarding School. The findings will be analyzed to reconstruct concepts based on empirical theory which have been presented on the theoretical basis and literature review in chapter II. Then the analysis tools for the findings of this field research are: 1) There are two types of strategies used in the Mambaul Falah Islamic boarding school in Tambilung in learning the Qur'an, namely individual classical and classical read-see; 2) The influencing factor of using Al-Qur'an learning strategies is the role of a teacher in teaching Al-Qur'an. From the presentation that has been studied by researchers that the Mambaul Falah Islamic Boarding School has a strategy for learning the Koran. Which is in accordance with Zarkasyi's strategy theory which says that there are three strategies for learning the Koran, namely the sorogan system, individual classical, and classical reading Simak